The long-time chronoamperometric current at an inlaid disk electrode - Bell, C; Howell, P; Stone, H; Lim, W; Siggers, J (2012)
Existing analytical solutions for the long-time chronoamperometric current response at an inlaid disk electrode are restricted to diffusion-limited currents due to extreme polarisation or reversible kinetics at the electrode surface. In this article, we derive an approximate analytical solution for the long-time-dependent current when the kinetics of the redox reaction at the electrode surface are quasi-reversible and the diffusion coefficients of the oxidant and reductant are different. We also detail a novel method for calculating the steady-state current. We show that our new method encapsulates and extends the existing solutions, and agrees with numerically simulated currents. © 2012 Elsevier B.V. All rights reserved.